A new species of Skeletocutis (Polyporales, Basidiomycota) from Yunnan of China - Bian, Lu-Sen; Zhao, Chang-Lin; Wu, Fang (Phytotaxa, 2016)
A new species of Polyporales, named as Skeletocutis yunnanensis, was collected on angiosperm wood in northern Yunnan Province, southwestern China. It is described based on morphological characteristics and molecular evidence. The species belongs to the Skeletocutis subincarnata complex, but differs morphologically from all known species of the genus by white, cream to buff pores surface, angular pores mostly 5–6 per mm with entire mouths, a dimitic hyphal structure both in trama and subiculum, generative hyphae in whole basidiocarps covered by fine crystals, skeletal hyphae unchanged in KOH, not agglutinated, allantoid basidiospores measured as 3.5–4.5 × 1.0–1.2 µm, and growth on angiosperm wood. Phylogenetic analysis based on the internal transcribed spacer (ITS) regions and nuclear large subunit (nLSU) ribosomal RNA gene regions indicated that the new species grouped with Skeletocutis and nested in the tyromyces clade.